2019
DOI: 10.3390/md17040201
|View full text |Cite
|
Sign up to set email alerts
|

Antitumoral Effect of Laurinterol on 3D Culture of Breast Cancer Explants

Abstract: Macroalgae represent an important source of bioactive compounds with a wide range of biotechnological applications. Overall, the discovery of effective cytotoxic compounds with pharmaceutical potential is a significant challenge, mostly because they are scarce in nature or their total synthesis is not efficient, while the bioprospecting models currently used do not predict clinical responses. Given this context, we used three-dimensional (3D) cultures of human breast cancer explants to evaluate the antitumoral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 61 publications
1
21
0
Order By: Relevance
“…Cultures of human breast cancer explants treated with laurinterol showed a heterogeneous response, probably related with the individual response of each tumor sample. The study supports the cytotoxic and antitumoral effects of 1 both in in vitro cell cultures as in ex vivo organotypic cultures 25 .…”
Section: Discussionsupporting
confidence: 76%
See 3 more Smart Citations
“…Cultures of human breast cancer explants treated with laurinterol showed a heterogeneous response, probably related with the individual response of each tumor sample. The study supports the cytotoxic and antitumoral effects of 1 both in in vitro cell cultures as in ex vivo organotypic cultures 25 .…”
Section: Discussionsupporting
confidence: 76%
“…Furthermore, the mitochondrial damage was also checked by measuring the generated ATP levels in 24 h. The observed results showed that laurinterol IC 90 treated amoebae presented a 97.36% decrease of ATP levels when compared to untreated cells. Moreover, since laurinterol has been reported as an inhibitor of the Na + /K + -ATPase sodium–potassium ion pump 25 , activity assays of known inhibitors including ouabain and furosemide were carried out. Amoebae showed to be ouabain-insensitive even at high concentrations of this product whereas furosemide showed an IC 50 of 0.71 ± 0.04 mM.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Among marine organisms, algae of the genus Laurencia are considered one of the richest sources of novel compounds with a wide range of bioactive properties, such as the brominated sesquiterpenes laurinterol (1) and aplysin (2) ( Figure 1) [10]. Laurinterol has been evaluated for its antibacterial [11][12][13], cytotoxic [13][14][15], antifouling [16], anti-Acanthamoeba [17], Na/K ATPase inhibition [18], insecticidal, and repellent properties [19]. Meanwhile, aplysin has shown moderate cytotoxic activity and has been evaluated for its mechanisms of action in different biological models [20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%